Institutions, relations, and outcomes : a framework and case stud ies for gender-aware planning - Kabeer, Naila; Subrahmanian, Ramya; Kali for Women (Organization) (New Delhi : Kali for Women, 1999)
With reference to India.
Includes bibliographical references.
Keywords: Kinship -- India; Family -- India; Social policy; Women -- India -- Social conditions; Women's rights -- India